2011
DOI: 10.2459/jcm.0b013e32834ae458
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of fragmented QRS in primary prevention implantable cardioverter defibrillator recipients with left ventricular dysfunction

Abstract: In ICD recipients for primary prevention of SCD, fQRS is not helpful in selecting a subgroup of patients who benefit from prophylactic ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 25 publications
1
26
1
1
Order By: Relevance
“…Fragmented QRS was not associated with increased risk of all-cause mortality, arrhythmic mortality and non-arrhythmic mortality. Similar conclusions were drawn from studies by Forleo et al [36].…”
Section: Discussionsupporting
confidence: 79%
“…Fragmented QRS was not associated with increased risk of all-cause mortality, arrhythmic mortality and non-arrhythmic mortality. Similar conclusions were drawn from studies by Forleo et al [36].…”
Section: Discussionsupporting
confidence: 79%
“…At 16.6 ± 10.2 months follow-up, fQRS was found to be a predictor of arrhythmic events, but not mortality. Additionally, in a retrospective study, Forleo et al 10 found that fQRS did not predict the arrhythmic events and mortality. Cheema et al 9 evaluated the association of fQRS with all-cause and arrhythmic mortality in 842 patients with moderate to severe left ventricular systolic dysfunction (ischemic or nonishemic etiology).…”
Section: Discussionmentioning
confidence: 97%
“…3 Fragmented QRS complex (fQRS), as a noninvasive prognostic marker on resting electrocardiography (ECG) emerged as a diagnostic and/or prognostic marker in several cardiovascular conditions. [8][9][10][11][12][13] So, in this study, we aimed to investigate the association of appropriate ICD shocks and all-cause mortality with the presence and extent of fQRS in patients with systolic heart failure who underwent ICD implantation for primary prophylaxis previously. [8][9][10][11][12][13] So, in this study, we aimed to investigate the association of appropriate ICD shocks and all-cause mortality with the presence and extent of fQRS in patients with systolic heart failure who underwent ICD implantation for primary prophylaxis previously.…”
mentioning
confidence: 99%
“…Fragmentation of the QRS complex (f‐QRS) on the 12‐lead electrocardiogram (ECG), defined as the presence of additional notches buried within the QRS, reflects derangement of ventricular conduction due to myocardial scar or fibrosis . f‐QRS may be associated with prior myocardial infarction, left ventricular dysfunction, and adverse arrhythmic events in various cardiac diseases; however, their utility to risk stratification strategies remains unclear . Addressing as yet unresolved issues in the evaluation of whether and to what extent heart rate change or/and mode of pacing affects the detection of f‐QRS might help to improve SCD risk prediction with the simple, inexpensive and easily available ECG.…”
Section: Introductionmentioning
confidence: 99%